Implementasi Strategi Layanan Teknologi Digital Banking dan Service Quality dalam Perspektif Nasabah pada Perbankan Syariah (Study kasus pada Bank Syariah Mandiri KCP Tomang) - Mamun, Sukron; Ningsih, Tri Hadmiatin (DPPM Universitas Pelita Bangsa, 2021)
In banking, service delivery is related to development real technology including Internet Banking, Phone banking, SMS Banking, Mobile Banking, ATM, and Service Quality, namely services provided by human resources in this case CS (Customer Service) such as interactions directly by providing services directly with good like service in good, polite and friendly language, it can improving banking quality in improving service quality towards customers. The research method that will be used in this research is descriptive method with a case study approach. The research that researchers made using a qualitative approach. Data collection techniques through: study literature, interviews, documentation, and observations. Based on the results interviews conducted, it can be concluded that implementation technology service strategy Digital Banking at Bank Syariah Mandiri KCP Tomang has implemented four main dimensions of Digital Banking (E-Serqual), meanwhile from the observation of the implementation of the Quality Service (Quality of service) given Customer Service Bank Syariah Mandiri KCP Tomang to customers, Customer Service has implemented 10 dimensions in its service to customers, apart from that based on the conclusion of the interview that Customer Service has also been guided by the five dimensions of service, this is based from the customer's perspective on the implementation of Quality Service (Quality services) provided by Customer Service at Bank Syariah Mandiri KCP Tomang and confirmed by the observations of researchers that all indicators are considered highly good and very satisfying.